Post-Hercynian ultrahigh-temperature tectono-metamorphic evolution of the Middle Atlas lower crust (central Morocco) revealed by metapelitic granulite xenoliths - A. El Maz; A. Vauchez; J.-M. Dautria (Solid Earth)
The study of metapelitic sillimanite- and garnet-bearing granulite xenoliths brought to the surface by the basanite of the 650 ka Tafraoute maar shed new light on the lower crust of the Tabular Middle Atlas (Morocco). Two main types of granulites are distinguished: (1) layered quartzo-feldspathic and (2) unlayered restitic. Mineralogy, petrology, P–T estimates, and electron backscatter diffraction (EBSD) data support that these granulites underwent two successive tectono-metamorphic events before their entrapment in lava. During the first event, probably the Hercynian orogeny, the Tafraoute lower crust acquired its foliation and primary paragenesis, likely including kyanite; it yields P and T conditions of 1.1 ± 0.1 GPa and 850–880 °C. The second event corresponds to a reheating up to ultrahigh temperatures (1050 ± 50 °C) under slightly lower-pressure conditions (0.9 ± 0.1 GPa). This led first to the transformation of kyanite into large prismatic sillimanite. The latter displays uncommon evidence of the dislocation creep deformation of a moderate intensity that points to a tectonic episode occurring after their formation. After deformation has stopped, a reaction between sillimanite and garnet resulted in the crystallization of orthopyroxene and spinel-deformation-free coronas around garnets. Approaching the peak of temperature, anhydrous partial melting of quartzo-feldspathic layers likely occurred, and the resulting felsic melt spread into the rocks. This reheating event might be the consequence of the Late Permian to Mid Jurassic rifting that preceded the formation of the Middle Atlas range, possibly associated with underplating of hot gabbroic magma. This event was followed by gradual cooling down to ∼ 800 °C, leading to static crystallization of the felsic melt in the quartzo-feldspathic granulites. The last event susceptible to have affected the lower crust is the alkali magmatism active in the Middle Atlas during the Mio-Plio-Quaternary. In this context, the origin of restitic granulites is questionable. It may result either from the thermal event associated with the pre-alpine rifting or from the emplacement of basaltic dikes in the lower crust before the Quaternary eruption of the Tafraoute volcano. During this eruption, the studied granulites were entrapped in the ascending lava and very quickly transferred up to the surface, triggering the formation of small vesicular glass pockets. This study highlights the contrasted post-Hercynian evolution of the lower crust in the northern coastal alpine orogen (Rif) and the Tabular Middle Atlas; the first one underwent a tectonic exhumation without reheating during the Alpine orogeny, while the second one is characterized by a reheating to ultrahigh temperature, probably during the pre-alpine rifting, but was probably not or only slightly affected by the alpine events.